2010
DOI: 10.1055/s-0030-1262507
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Pulmonary Hypertension of the Newborn Is Associated with Mode of Delivery and Not with Maternal Use of Selective Serotonin Reuptake Inhibitors

Abstract: We sought to determine if maternal use of selective serotonin reuptake inhibitors (SSRIs) in the second half of pregnancy is associated with persistent pulmonary hypertension of the newborn (PPHN). We performed a case-controlled study (1:6 ratio) of infants delivered at Madigan Army Medical Center with primary PPHN from 2003 through 2009. Study and control patients were compared for the following clinical factors: SSRI use after 20 weeks gestation, mode of delivery, maternal disease, body mass index, tobacco u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 19 publications
2
80
1
Order By: Relevance
“…7,8 Based on a review of additional studies with conflicting findings (2 studies reported an increase in risk, whereas 3 did not), the FDA concluded in 2011 that it was premature to reach any conclusion about a possible link between SSRI use in pregnancy and PPHN and updated the advisory accordingly. [9][10][11][12][13] The negative studies tended to be small, raising the possibility that they had insufficient power to detect an increased risk. 10,11 Given the ongoing controversy regarding the association between SSRI exposure in late pregnancy and the risk of this highly morbid pregnancy outcome, we examined the risk of The approach used for the development of our study cohort has previously been described in detail.…”
Section: Hhs Public Accessmentioning
confidence: 99%
“…7,8 Based on a review of additional studies with conflicting findings (2 studies reported an increase in risk, whereas 3 did not), the FDA concluded in 2011 that it was premature to reach any conclusion about a possible link between SSRI use in pregnancy and PPHN and updated the advisory accordingly. [9][10][11][12][13] The negative studies tended to be small, raising the possibility that they had insufficient power to detect an increased risk. 10,11 Given the ongoing controversy regarding the association between SSRI exposure in late pregnancy and the risk of this highly morbid pregnancy outcome, we examined the risk of The approach used for the development of our study cohort has previously been described in detail.…”
Section: Hhs Public Accessmentioning
confidence: 99%
“…Normally, PVR drops by half within the first two days of life in full-term newborns. Failure of PVR to drop is associated with multiple factors such as abnormal lung development, maldevelopment of the pulmonary vasculature, premature delivery, mode of delivery, meconium aspiration, maternal fever, maternal pulmonary disease and maternal use of selective serotonin update inhibitors [60][61][62]. In older children with IPAH, intimal hyperplasia and occlusive changes are found in pulmonary arterioles.…”
Section: Cell Proliferation and Apoptosismentioning
confidence: 99%
“…48,49,64 Data are also conflicting regarding the relationship between antenatal antidepressant exposure and other neonatal outcomes such as spontaneous abortion, birth weight, persistent pulmonary hypertension, and autism spectrum disorders. 23,26,35,47,[50][51][52][53][54][55][56][57]60,[65][66][67][68][69] Specific information on the risk of other neonatal outcomes in fetuses exposed to clomipramine is lacking. The limited available data suggest that similar to SSRIs, TCAs may be associated with PTB and PNAS.…”
Section: Congenital Malformationsmentioning
confidence: 99%